Riluzole treatment, survival and diagnostic criteria in Parkinson plus disorders: The NNIPPS Study - Bensimon, Gilbert (Oxford University Press, 2009)
Parkinson plus diseases, comprising mainly progressive supranuclear palsy (PSP) and multiple system atrophy (MSA) are rare neurodegenerative conditions. We designed a double-blind randomized placebo-controlled trial of riluzole as a potential disease-modifying agent in Parkinson plus disorders (NNIPPS: Neuroprotection and Natural History in Parkinson Plus Syndromes). We analysed the accuracy of our clinical diagnostic criteria, and studied prognostic factors for survival. Patients with an akinetic-rigid syndrome diagnosed as having PSP or MSA according to modified consensus diagnostic criteria were considered for inclusion. The psychometric validity (convergent and predictive) of the NNIPPS diagnostic criteria were tested prospectively by clinical and pathological assessments. The study was powered to detect a 40% decrease in relative risk of death within PSP or MSA strata. Patients were randomized to riluzole or matched placebo daily and followed up to 36 months. The primary endpoint was survival. Secondary efficacy outcomes were rates of disease progression assessed by functional measures. A total of 767 patients were randomized and 760 qualified for the Intent to Treat (ITT) analysis, stratified at entry as PSP (362 patients) or MSA (398 patients). Median follow-up was 1095 days (range 249–1095). During the study, 342 patients died and 112 brains were examined for pathology. NNIPPS diagnostic criteria showed for both PSP and MSA excellent convergent validity with the investigators’ assessment of diagnostic probability (point-biserial correlation: MSA r(pb) = 0.93, P < 0.0001; PSP, r(pb) = 0.95, P < 0.0001), and excellent predictive validity against histopathology [sensitivity and specificity (95% CI) for PSP 0.95 (0.88–0.98) and 0.84 (0.77–0.87); and for MSA 0.96 (0.88–0.99) and 0.91 (0.86–0.93)]. There was no evidence of a drug effect on survival in the PSP or MSA strata (3 year Kaplan–Meier estimates PSP-riluzole: 0.51, PSP-placebo: 0.50; MSA-riluzole: 0.53, MSA-placebo: 0.58; P = 0.66 and P = 0.48 by the log-rank test, respectively), or in the population as a whole (P = 0.42, by the stratified-log-rank test). Likewise, rate of progression was similar in both treatment groups. There were no unexpected adverse effects of riluzole, and no significant safety concerns. Riluzole did not have a significant effect on survival or rate of functional deterioration in PSP or MSA, although the study reached over 80% power to detect the hypothesized drug effect within strata. The NNIPPS diagnostic criteria were consistent and valid. They can be used to distinguish between PSP and MSA with high accuracy, and should facilitate research into these conditions relatively early in their evolution.